Structure Characterization of Polysaccharide from Chinese Yam (Dioscorea opposite Thunb.) and Its Growth-Promoting Effects on Streptococcus thermophilus - Jia Ouyang (MDPI AG, 2021)
To clarify the mechanisms underlying the growth-promoting effects of yam polysaccharide on Streptococcus thermophilus (S. thermophilus), the yam polysaccharide was extracted using a deep eutectic solvents (DESs) method and separated into four fractions by DEAE-cellulose 52. These fractions were used as the alternative carbon source to substitute lactose to compare their growth-promoting effects on S. thermophilus. Furthermore, their molecular weight, monosaccharide and functional groups’ composition, microscopic forms and other basic structure characterizations were analyzed. The results showed that all the fractions could significantly promote S. thermophilus growth, and fractions exhibited significantly different growth-promoting effects, whose viable count increased by 6.14, 6.03, 11.48 and 11.29%, respectively, relative to those in the M17 broth medium. Structure-activity relationship analysis revealed that the high growth-promoting activity of yam polysaccharide might be more dependent on the higher molecular weight, the higher galacturonic acid content and its complex spatial configuration, and the existence of β-glycosides would make the yam polysaccharide have a better growth-promoting effect on S. thermophilus.